A Cultural Mind That Computes - Li, Weihua; Wu, Jialei (Journal of Educational Research and Policies, 2024)
The issue of nature vs. nurture in the field of education has enjoyed a long history of debate and discussion. In this article, we try to approach it from the perspectives of both cognitive neuroscience and developmental psychology in the attempt of developing a new cognitive-cultural perspective of education. We argue that education is essentially a cultural practice that could be viewed as a type of information processing due to its tight connection to language and cognitive process. We also bring forth a new dual-narrative framework that has the potential of explaining cultural phenomena related to issues faced in compatibility and identity development, both of which in our opinion are quite urgent matters that need to be addressed and discussed more in education.